Histomorphological assessment of non-neoplastic renal diseases at autopsy: an institutional experience in Southwestern Nigeria (2021)
Background Autopsy remains an invaluable resource for medical education and establishing diagnosis of diseases that were missed prior to death. Many patients on admission in hospitals suffer kidney diseases that may contribute to their morbidity and/or mortality. The kidneys from autopsies provide opportunity to diagnose and understand some of these non-neoplastic renal lesions. This study aimed to present the frequency of non-neoplastic renal diseases at autopsy. Methods We conducted a five-year retrospective review of post-mortem records of deceased who had autopsy. Data such as age, sex, cause of death, and kidney lesions were extracted from the post-mortem records and clinical details were gotten from the clinical summaries in the autopsy reports. The kidneys were examined for pathological findings that were then classified into glomerular, tubulointerstitial (tubulointerstitial nephritis and other tubular lesions such as tubular necrosis, casts and fibrosis) and vascular lesions. Results A total of seventy (70) cases met the inclusion criteria with 91.4% having significant non- neoplastic renal lesions. The mean age of the deceased was 57.7years (18years – 91years). Males accounted for 65.7% of the cases. Glomerular lesions were seen in 84.3% of the cases, tubulointerstitial nephritis in 41.6% of cases, vascular lesions were seen in 30% of the cases and other tubular lesions (such as stones, casts and tubular necrosis) were seen in 52.9% of the cases. Cardiovascular diseases and infections were the major causes of death in these patients, accounting for 40% and 27% respectively. Renal diseases were attributed to immediate cause of death in 10% of the cases. Conclusion The kidney at autopsy provides a valuable renal pathology educational tool, as a wide range of medical renal lesions can be seen from kidneys examined at post mortem.